Poverty in a Rising Africa - Beegle, Kathleen; Christiaensen, Luc; Dabalen, Andrew; Gaddis, Isis (Washington, DC: World Bank, 2015)
Perceptions of Africa have changed dramatically. Viewed as a continent of wars, famines and entrenched poverty in the late 1990s, there is now a focus on “Africa rising” and an “African 21st century.” Two decades of unprecedented economic growth in Africa should have brought substantial improvements in well-being. Whether or not they did, remains unclear given the poor quality of the data, the nature of the growth process (especially the role of natural resources), conflicts that affect part of the region, and high population growth.